Human papillomavirus vaccine effectiveness by number of doses: Systematic review of data from national immunization programs. Issue 32 (6th August 2018) - Markowitz, Lauri E.; Drolet, Melanie; Perez, Norma; Jit, Mark; Brisson, Marc
Abstract: Background: Human papillomavirus (HPV) vaccines were first licensed as a three-dose series; a two-dose series is now recommended in some age groups and there is interest in possible one-dose vaccination. Methods: We conducted a systematic literature review of HPV vaccine effectiveness by number of doses, including assessment of biases and impact of varying buffer periods (time between vaccination and outcome counting). Results: Of 3787 articles identified, 26 full articles were assessed and 14 included in our review. All studies were conducted within the context of recommended three-dose schedules of bivalent (3) or quadrivalent HPV vaccine (11). Two evaluated effectiveness for prevention of HPV prevalence, six anogenital warts, and six abnormal cervical cytology or histology. Many studies found differences between three-, two- and one-dose vaccine recipients, indicating possible differences in HPV exposure prior to vaccination or in risk behavior. Adjusted or stratified analyses were conducted to control for potential confounding. All studies found significant vaccine effectiveness with three doses, 11 with two doses at various intervals, and six with one dose. Most studies showed a relationship (not always statistically significant) between effectiveness and number of doses, with greater decreases in HPV-related outcomes with three, followed by two and one dose(s). Few studies conducted formal comparisons of three vs fewer doses. Three of four studies that examined buffer periods found higher effectiveness and a smaller difference by number of doses with longer periods. Conclusion: Most post-licensure studies report highest effectiveness with three doses; some found no statistically significant difference between two and three doses. Additionally, almost half found some effectiveness with one dose. Several biases impact estimates, with most biasing two- and one-dose results away from showing effectiveness. Future effectiveness studies, examining persons vaccinated prior to sexual activity and using methods to reduce potential sources of bias, can help inform vaccination policy.